Talc as raw material for cementitious products formulation - C.J. Ngally Sabouang; J.A. Mbey; Liboum; F. Thomas; D. Njopwouo (Journal of Asian Ceramic Societies, 2014)
This study reports the characterization of a talc from Cameroon as a possible source material for cement formulation. To that end, the talc sample was characterized and mixed with a solution of sodium polyphosphate to formulate the cementitious products. Addition of magnesia (MgO) was done to analyze the effect of available MgO on the products. Fourier transform infrared, X-rays diffraction, linear shrinkage, compressive strength and scanning electron microscopy were used to analyze the products. The compressive strength increased with addition of MgO and the linear shrinkage decreased. All the analyses indicate that talc is a raw material of interest in cementitious products formulation; however, the inclusion of the MgO is a key factor for a better performance of the products.